Mentoring: To ease one into something, something not yet one's own. Issue 3 (1st December 2016) - O'Donoghue, Donal; Lenz Kothe, Elsa; Thomas, Kate; Berard, Marie-France; Smith, Blake; Ryoo, Anna
This article uses a conversation as the point of departure for considering the nature, qualities and scope of mentorship, and what mentorship does, enables and denies within academic relationships. Six art education colleagues gather to explore concepts, potentialities, places and practices of mentoring in a face-to-face interaction that leads to further musings through a collective writing process. From tweets to personal testimony, this subjective and philosophical unfolding negotiates possible routes for navigating some of the complexities, qualities, emotional landscapes, and interactions of the mentor/mentee relationship. We aim to challenge our own assumptions and expectations by asking critical questions, creating openings for other ways of knowing, and imagining what else might become possible when mentorship helps ease someone into something not yet one's own.